Error Analysis in Students’ Writing Composition - Agung Pranoto Kadiatmaja (STAI Ali bin Abi Thalib Surabaya, 2021)
To recognize the students’ difficulties, this research analyzes errors in Students’ writing composition of Passive Voice. This study of error (error analysis) is part of an investigation of the process of English language learning. This research is to find the types of error analysis in students’ writing composition and to find the most dominant types of error analysis in students’ writing composition of passive voice. This research is qualitatively accomplished to look into errors in the second language acquisition. This research focused on the qualitative research by using document analysis to collect empirical data from the students’ writing. This method is applied to get the accurate data collection. The object of the research is students’ writing composition randomly taken from sixteen ESP students of Strata 1 – Arabic Department of STAI Ali bin Abi Thalib Surabaya. The researcher investigates more details by using surface strategy taxonomy to get the result of this error analysis. It is limited on the students’ passive sentences error in writing composition consisting of four error types: omission, addition, misformation, and misordering. Finally, after identifying the entire data and analyzing the research findings, it can be summarized that the types of passive voice errors produced by the students are (1) omission that occurred 24 times or 51,06% of all, (2) addition that occurred 15 times or 31,96% of all, (3) misordering that occurred 5 times or 10,64% of all, and (4) misformation that occurred 3 times or 6,38% of all. According to the research findings, the most dominant type of passive voice error is omission.